Feasibility in Using Technological Resources for Implementing the Environmental Culture Cross-Cutting Factor for Sustainable Development in the Costa Rican Basic General Education - Lorna Matarrita-Román; Jessica Serrano-Calvo; María Isabel Torres-Salas; Giselle León-León (Universidad Nacional, Costa Rica, 2012)
The purpose of this research was to analyze whether the use of technological resources may be feasible in the implementation of the environmental culture cross-cutting factor for sustainable development, which focuses on environmental issues related to the contents of the Science study program for the seventh year of the basic general education. The research design is qualitative with a dominant approach and uses some quantitative elements specifically in the design of instruments and some data analysis techniques. The type of study was developed with a multi-method approach; a trend that has been shaping a research style which integrates various methods in a single design. For this, we identified the didactic strategies and their relationship to both, technology and the environmental axis for sustainable development, used by six Science teachers of the 7th grade, in public institutions of the province of Heredia, Central Valley, Costa Rica, as well as the opinion of 20 students from that same grade. The main results include the opinions of the students, who showed a considerable interest in classes where technological resources are used. However, teachers do not show great interest or positive opinions on this matter; in addition, they are not well trained on the use of technological resources. It was also identified that the teaching personal who participated in the study do not develop this curricular axis.